Impact of Thermal Conductivity on Energy Technologies - Shahzad, Aamir (IntechOpen, 2018)
This book is intended to provide a deep understanding on the advanced treatments of thermal properties of materials through experimental, theoretical, and computational techniques. This area of interest is being taught in most universities and institutions at the graduate and postgraduate levels. Moreover, the increasing modern technical and social interest in energy has made the study of thermal properties more significant and exciting in the recent years. This book shares with the international community a sense of global motivation and collaboration on the subject of thermal conductivity and its wide spread applications in modern technologies. This book presents new results from leading laboratories and researchers on topics including materials, thermal insulation, modeling, steady and transient measurements, and thermal expansion. The materials of interest range from nanometers to meters, bringing together ideas and results from across the research field.